Understanding persistence in bulimia nervosa: a 5-year naturalistic study. - Fairburn, C; Stice, E; Cooper, Z; Doll, H; Norman, P; O'Connor, M (2003)
Bulimia nervosa shows a marked tendency to persist, suggesting that powerful maintaining mechanisms operate. Using data from a prospective, 5-year, study of the natural course of 102 people with bulimia nervosa, the authors sought to identify predictors of persistence and to test specific hypotheses derived from the cognitive-behavioral theory of the persistence of bulimia nervosa. The results of both sets of analyses were consistent with the theory, with the degree of overevaluation of shape and weight and a history of childhood obesity predicting a persistent course. There was also support for the central prediction of the cognitive-behavioral theory. These findings suggest that the mechanisms specified by the theory influence its longer term natural course.